The Viscosity Of Blast- Furnace Slag - Alexander Field (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
INTRODUCTION THE Bureau of Mines is investigating the problem of slag viscosity, its variation with the temperature and with the composition of the slag, and its effect upon the distribution of the sulphur between molten iron and slag, as introductory to a series of contributions to the theory of the metallurgical processes. The method of measurement, viscosity, apparatus, furnace and other accessories mentioned in this paper have been described fully in a Bureau of Mines report.1 THE LITERATURE ON SLAG VISCOSITY The viscosity of blast-furnace slag had not been measured previous to the investigation described in this report. A number of investigators have determined the "fusibility," or softening temperature, of slags by means of the cone method or, other deformation method, but these methods supply only limited information regarding the temperature-viscosity relations.-of the slag in question. Any deformation method that may be employed indicates only the temperature at which the slag attains a more or less definite viscosity, the magnitude of the value obtained depending on the method used. For details of the various methods used by different investigators, see, the Bureau of Mines paper already referred to. An isolated measurement by Doelter on a single mixture at 1,300° C. represents the highest temperature reached in the various viscosity investigations previous to those described in this report, in which results have been referred to absolute units. Arbitrary deformation tests have of course been made at much higher temperatures.